CRISPR-Cas9 Arabidopsis mutants of genes for ARPC1 and ARPC3 subunits of ARP2/3 complex reveal differential roles of complex subunits - Bellinvia, Erica; García-González, Judith; Cifrová, Petra; Martinek, Jan; Sikorová, Lenka; Havelková, Lenka; Schwarzerová, Kateřina (Scientific reports, 2022)
Protein complex Arp2/3 has a conserved role in the nucleation of branched actin filaments. It is constituted of seven subunits, including actin-like subunits ARP2 and ARP3 plus five other subunits called Arp2/3 Complex Component 1 to 5, which are not related to actin. Knock-out plant mutants lacking individual plant ARP2/3 subunits have a typical phenotype of distorted trichomes, altered pavement cells shape and defects in cell adhesion. While knock-out mutant Arabidopsis plants for most ARP2/3 subunits have been characterized before, Arabidopsis plant mutants missing ARPC1 and ARPC3 subunits have not yet been described. Using CRISPR/Cas9, we generated knock-out mutants lacking ARPC1 and ARPC3 subunits. We confirmed that the loss of ARPC1 subunits results in the typical ARP2/3 mutant phenotype. However, the mutants lacking ARPC3 subunits resulted in plants with surprisingly different phenotypes. Our results suggest that plant ARP2/3 complex function in trichome shaping does not require ARPC3 subunit, while the fully assembled complex is necessary for the establishment of correct cell adhesion in the epidermis.
Keywords: CRISPR-Cas systémy; protein 2 související s aktinem; protein 3 související s aktinem; CRISPR-Cas Systems; Actins; Actin-Related Protein 2-3 Complex; Actin-Related Protein 3; Arabidopsis; komplex proteinů 2-3 souvisejících s aktinem; Actin-Related Protein 2; aktiny